Exploitation of Child Domestic Workers in Ngenger Culture of Javanese Society in Indonesia - Haryono, Tri Joko Sri; Kinasih, Sri Endah; Mas'udah, Siti (Journal of international women's studies, 2024)
This study explains a Javanese cultural practice called ngenger--when girls volunteer to be domestic servants in exchange for educational benefits--as a form of exploitation of labor. The purpose of this study is to understand this Javanese tradition from the perspective of Gender Anthropology. This research is a descriptive study using a qualitative method. The location of the study was in Surabaya and the city of Malang, East Java, and was conducted by collecting data in the form of observations and in-depth interviews. The informants for this study were girls who are domestic workers, parents of the child domestic workers, and the recipient parents of these child domestic workers. This study shows that ngenger girls employed as domestic workers are exploited since they lose almost all of their rights. The ways in which ngenger girls are exploited include having low wages, lacking bargaining power, being forced to be obedient, lacking the courage to claim their rights, not daring to complain to anyone, and continuing to serve the recipients. The condition where the ngenger girls do not have bargaining position over the recipients of their labor is precisely what makes this practice a form of exploitation. The relationship between girls and the recipient families is a patron-client relationship. The patron-client relation should be a reciprocal relationship that is mutually beneficial. A recipient patron of a ngenger girl has the responsibility to fulfill the needs of the girl as a client, and, in return, the client must give her loyalty to her patron. Patron-client relations are economic relations where profits must be achieved, which makes exploitation possible. In fact, ngenger girls do not get the fulfillment of basic needs, protection, and good education, but they still continue to be loyal to the recipient parents. This circumstance is what makes the relationship in ngenger culture an unfair and exploitative relationship.